Systena silvestrii Bechyné (Coleoptera: Chrysomelidae): Redescription, New distribution and adult host records - Cabrera, Nora Clara (2007)
In order to search for natural enemies of alligator wee (Alternanthera philoxeroides (Martius) Grisebach (Amaranthaceae) The flea beetle Systena silvestrii Bechyné 1957 was stidied. The female is described and the holotype male is redescribed adding new diagnostic characters: mouthparts, hind wings, metendosternite, male and female genitalia. Differences in color patterns between S. silvestrii, S. marcapatensis Bechyné, S. scurra scurra Scherer and S. scurra ajonjoli Bechyné &Bechyné are considered. This flea beetle was collected mostly on alligator weed but also on Phyla canescens (Vebenaceae) in Argentina, Uruguay, Paraguay and Brazil. Therefore, is highly recommended further evaluation prior to its consideration as a potential biological control agents of A. philoxeroides.